Determining digital literacy among teacher from gender perspective through the Rasch model - Indah Wigati; Faisal Faisal; Resti Tri Astuti (Journal of Education and Learning (EduLearn), 2022)
Advances in technology and the implementation of online learning require all parties in educational institutions, especially teachers, to be able to use technology. Digital literacy skills are needed to support the learning process. The purpose of this study was to measure the digital literacy skills of teachers through the Rasch model from a gender perspective during the coronavirus disease 2019 (COVID-19) pandemic at Madrasah Aliyah Negeri Palembang, Indonesia. A quantitative research method using Rasch analysis was applied. The results showed that the ability of teachers in digital literacy can be categorized as very high (three people), high (28 people), moderate (63 people), and low (two people) and showed that there are no question items that only favor one of the genders. The results showed that the male teachers in this study had a lower level of digital literacy skills than the female teachers.